0486 Impact of Intrinsic Factors on Efficacy of Lemborexant: Subgroup Analyses of SUNRISE-2. (27th May 2020) - Moline, M; Inoue, Y; Kubota, N; Pinner, K; Perdomo, C; Yardley, J
Abstract: Introduction: Lemborexant (LEM), a dual orexin receptor antagonist, demonstrated significant benefits vs placebo on patient-reported sleep outcomes in adults age ≥18y in SUNRISE-2 (NCT02952820; E2006-G000-303). The impact of intrinsic factors (sex, race, and region) on LEM efficacy outcomes was assessed. Methods: SUNRISE-2 was a randomized, double-blind, global phase 3 study in adults age ≥18y with insomnia disorder (Full Analysis Set, n=949). Subjects received placebo (n=318) or LEM (5mg [LEM5], n=316; 10mg [LEM10]; n=315) for 6 months. At 6 months, placebo subjects were rerandomized to LEM for another 6 months (not reported here); LEM subjects remained on their assigned dose. Sleep diary-based (subjective) sleep onset latency (sSOL) and wake after sleep onset (sWASO) were assessed for prespecified patient subgroups including: sex (male [n=302], female [n=647]), race (white [n=679], black [n=76], Asian [n=178]), and region (North America [n=302], Europe/New Zealand [n=483], Asia [n=164]). Analyses were not controlled for multiplicity. Results: LEM5 and LEM10 provided numerically greater median reductions (improvement) from baseline in sSOL vs placebo at 6 months in across all subgroups examined. Also, LEM5 and LEM10 led to mean reductions (improvement) from baseline at 6 months in sWASO for all subgroups. While several subgroups had small numbers of subjects, changes from baseline in sSOL and sWASO were in the direction of improvement in the majority of subgroups. Pharmacokinetic analyses showed no important differences in exposure by these factors. Conclusion: LEM treatment demonstrated efficacy in improving sSOL and sWASO across patient subgroups, supporting common dosing instructions for both sexes and all races. Support: Eisai Inc.